Sheet provided with heat-insulating layer and pressure-sensitive adhesive layer
By reasonably proportioning thermally expandable and non-thermal expandable organic hollow particles in the insulating layer and using specific matrix polymers, the problem of degradation of thermal insulation in the reflow welding process of non-volatile memory is solved, and a stable thermal insulation is achieved Layer design.
Patent Information
- Application Number
- CN202380037099.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-14
AI Technical Summary
When the nonvolatile memory is exposed to a high temperature environment during the reflow soldering process, the organic hollow particles in the insulating material may shrink, resulting in a decrease in thermal insulation and affecting the quality of the memory.
Using an insulating layer containing thermally expandable and non-thermal expandable organic hollow particles, the volume ratio of the first and second hollow particles is reasonably proportioned in the insulating layer, and a specific matrix polymer is used to form a low elasticity and excellent elongation. Insulating layer to suppress the decline of thermal insulation.
It effectively suppresses the degradation of the insulation layer in a high-temperature environment, and ensures the stability of the quality of the memory in the reflow welding process.
Smart Images

Figure CN119317537A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sheet material having a heat insulating layer and a pressure-sensitive adhesive layer. Background Art
[0002] Non-volatile memory, which features low power consumption and high-speed read / write, has attracted much attention as a next-generation memory. For example, phase change memory (PCM), magnetoresistive RAM (MRAM), resistive random access memory (ReRAM), etc. are known. Non-volatile memory is not heat-resistant, and quality maintenance when exposed to high temperature environments during the reflow soldering process during installation has become an issue.
[0003] In response to this issue, for example, patent document 1 discloses a method for manufacturing a magnetic recording device, which includes a reflow process, and the reflow process includes: a first step of providing an insulating material on the surface of the magnetic recording device exposed in a reflow furnace; a second step of passing the magnetic recording device provided with the insulating material through the reflow furnace and heating the magnetic recording device; and a third step of removing the insulating material from the heated magnetic recording device.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-224663 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] The inventors of the present invention have designed a sheet having an insulating layer and a pressure-sensitive adhesive layer containing organic hollow particles and a matrix polymer as a thermal insulation material used in a reflow soldering process. However, it has been clarified that if the sheet is exposed to a high temperature environment (e.g., above 180°C) during the reflow soldering process, the organic hollow particles contained in the sheet may shrink, and as a result, the thermal insulation of the sheet may decrease.
[0009] Therefore, an object of one aspect of the present invention is to provide a sheet material capable of suppressing a decrease in thermal insulation properties when exposed to a high-temperature environment.
[0010] Means for solving technical problems
[0011] The present inventors have conducted intensive research and found that, in a sheet having a heat-insulating layer and a pressure-sensitive adhesive layer, the heat-insulating layer can suppress the decrease in heat insulation when exposed to a high temperature environment by containing both heat-expandable organic hollow particles and hollow particles other than heat-expandable organic hollow particles. The present invention provides the following [1] to [4] in several aspects.
[0012] [1] A sheet comprising a heat insulating layer and a pressure-sensitive adhesive layer, wherein the heat insulating layer contains first hollow particles which are heat-expandable organic hollow particles, second hollow particles which are organic hollow particles other than the first hollow particles, and a matrix polymer.
[0013] [2] The sheet according to [1], wherein the content of the first hollow particles is 1.5% by volume or more based on the total volume of the heat insulating layer.
[0014] [3] The sheet according to [1] or [2], wherein the volume ratio of the content of the second hollow particles to the content of the first hollow particles is 45 or less.
[0015] [4] The sheet according to any one of [1] to [3], wherein the matrix polymer contains a compound represented by the following formula (1) as a monomer unit,
[0016]
[0017] In formula (1), R 11 and R 12 Each independently represents a hydrogen atom or a methyl group, R 13 It represents a divalent group having a polyoxyalkylene chain.
[0018] Effects of the Invention
[0019] According to one aspect of the present invention, it is possible to provide a sheet material capable of suppressing a decrease in heat insulating properties when exposed to a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic cross-sectional view showing one embodiment of a sheet. DETAILED DESCRIPTION
[0021] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0022] The term "(meth)acryloyl" in the present specification refers to "acryloyl" and its corresponding "methacryloyl", and the same also applies to "(meth)acrylate", "(meth)acrylic acid" and the like.
[0023] The weight average molecular weight (Mw) in this specification refers to a value measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as a standard substance.
[0024] ·Measurement equipment: HLC-8320GPC (product name, manufactured by TOSOH CORPORATION)
[0025] Analytical column: TSKgel SuperMultipore HZ-H (3 connected) (product name, manufactured by TOSOH CORPORATION)
[0026] Guard column: TSKguardcolumn SuperMP(HZ)-H (product name, manufactured by TOSOH CORPORATION)
[0027] Eluent: THF
[0028] ·Measurement temperature: 25℃
[0029] Figure 1 This is a schematic cross-sectional view showing one embodiment of a sheet. Figure 1 The sheet material 10 shown includes a heat insulating layer 11 and a pressure-sensitive adhesive layer 12. The heat insulating layer 11 and the pressure-sensitive adhesive layer 12 may be laminated in contact with each other.
[0030] The heat insulating layer 11 contains first hollow particles 111 which are heat-expandable organic hollow particles, second hollow particles 112 which are organic hollow particles other than the first hollow particles, and a matrix polymer 113 .
[0031] The first hollow particle 111 has a shell and a hollow portion. The first hollow particle 111 is an organic hollow particle (thermally expansive) that expands due to heat. The thermally expansive organic hollow particles in this specification refer to organic hollow particles whose maximum volume expansion ratio relative to the volume at 25°C is more than 10 times. In the case where the thermal insulation layer 11 contains the first hollow particle 111, in the reflow process, even if the second hollow particle 112 described later shrinks and the volume of the hollow portion decreases, the first hollow particle 111 also expands due to heat, thereby increasing the volume of the hollow portion. Therefore, as a whole, the thermal insulation layer 11 can suppress the reduction in the volume of the hollow portion of the hollow particles that contribute to thermal insulation. As a result, the thermal insulation of the thermal insulation layer 11 (sheet 10) can be suppressed from decreasing.
[0032] The maximum volume expansion ratio of the first hollow particle 111 is measured by thermomechanical analysis (TMA) as the ratio of the maximum volume of the first hollow particle 111 when the temperature is increased at a heating rate of 10° C. / min to the volume at 25° C. (maximum volume / volume at 25° C.). The maximum volume expansion ratio of the first hollow particle 111 may be, for example, 20 times or more, 30 times or more, or 40 times or more, or 120 times or less.
[0033] The shell of the first hollow particle 111 is composed of an organic material. The shell of the first hollow particle 111 is preferably composed of a polymer, and more preferably composed of a thermoplastic polymer. At this time, since the shell softens due to heating, even if the liquid contained in the hollow portion is vaporized and the internal pressure rises, the hollow particle is not easy to break and is easy to expand. The thermoplastic polymer can be, for example, a polymer containing acrylonitrile, vinylidene chloride, etc. as monomer units. The thickness of the shell can be more than 2μm, and can also be less than 15μm.
[0034] The hollow portion of the first hollow particle 111, for example, contains a liquid. The first hollow particle 111, for example, contains a liquid at normal temperature and pressure (for example, at least at atmospheric pressure and 30°C). The liquid is appropriately selected, for example, according to the heating temperature in the reflow process and the shrinkage start temperature of the second hollow particle 112 described later. The liquid is, for example, a liquid that vaporizes at a temperature below the highest heating temperature in the reflow process. The liquid can be a liquid that vaporizes at a temperature below the shrinkage start temperature of the second hollow particle 112. The liquid can be, for example, a hydrocarbon having a boiling point (under atmospheric pressure) of 50°C or more, 100°C or more, 150°C or more, or 200°C or more. In addition to the above-mentioned liquid, the hollow portion of the first hollow particle 111 may also contain a gas.
[0035] As the components contained in the hollow part of the first hollow particle 111, there can be mentioned, for example, hydrocarbons such as propane, propylene, butene, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, isohexane, heptane, isooctane, n-octane, isoalkanes (carbon number: 10 to 13), and petroleum ether; low-boiling point compounds such as methane halides and tetraalkylsilane; and compounds that are gasified by thermal decomposition such as azodicarbonamide.
[0036] The average particle size of the first hollow particles 111 may be 5 μm or 10 μm or less, or 50 μm, 40 μm or less, or 30 μm or less. The average particle size of the first hollow particles 111 is measured by a laser diffraction / scattering method (for example, using “SALD-7500nano” manufactured by SHIMADZU CORPORATION).
[0037] From the viewpoint that the sheet 10 is more preferably used as an insulating material in a reflow soldering process (usually heated to 260°C), the expansion start temperature of the first hollow particle 111 is preferably below the contraction start temperature of the second hollow particle 112 described later. The expansion start temperature of the first hollow particle 111 is preferably above 150°C or above 180°C, and preferably below 260°C, below 240°C, below 220°C or below 200°C. The expansion start temperature of the first hollow particle 111 refers to the temperature of the intersection of the tangent of the point where a volume change of more than 3 times / 5°C is produced and the straight line (horizontal axis) where the volume change is zero (initial volume) in the curve of temperature (horizontal axis)-volume change (vertical axis) when the temperature is increased at a heating rate of 10°C / min by thermomechanical analysis (TMA).
[0038] From the viewpoint that the sheet 10 is more preferably used as an insulating material in the reflow process, the maximum expansion temperature of the first hollow particle 111 is preferably 100° C. or more, 150° C. or more, 200° C. or more, or 210° C. or more, and preferably 290° C. or less, 280° C. or less, or 270° C. or less. The maximum expansion temperature of the first hollow particle 111 refers to the temperature at which the first hollow particle 111 exhibits the above-mentioned maximum volume expansion ratio.
[0039] From the viewpoint of further suppressing the decrease in the thermal insulation properties of the sheet 10, the content of the first hollow particles 111 (the content at atmospheric pressure and 30°C. The same applies hereinafter) is preferably 1 mass % or more, more preferably 2 mass % or more, further preferably 4 mass % or more, and particularly preferably 5 mass % or more, and can be 20 mass % or less or 15 mass % or less, based on the total mass of the thermal insulation layer 11.
[0040] From the viewpoint of further suppressing the decrease in the thermal insulation of the sheet 10, the content of the first hollow particles 111 is preferably 0.5% by volume or more, more preferably 1.0% by volume or more, and further preferably 1.5% by volume or more, based on the total volume of the thermal insulation layer 11. From the viewpoint of suppressing excessive expansion of the volume of the sheet 10, the content of the first hollow particles 111 can be 10% by volume or less, 7% by volume or less, 5% by volume or less, or 4% by volume or less, based on the total volume of the thermal insulation layer 11.
[0041] The second hollow particle 112 has a shell and a hollow portion. The second hollow particle 112 is an organic hollow particle other than the first hollow particle 111. That is, the second hollow particle 112 is an organic hollow particle with a maximum volume expansion ratio of less than 10 times relative to the volume at 25°C. By using the second hollow particle 112, the thermal insulation of the insulation layer 11 is improved, and the sheet 10 can be preferably used as an insulation material. The maximum volume expansion ratio of the second hollow particle 112 is measured by the same method as the maximum volume expansion ratio of the first hollow particle.
[0042] The shell of the second hollow particle 112 is composed of an organic material. The shell of the second hollow particle 112 is preferably composed of a polymer, more preferably composed of a thermoplastic polymer. In this case, the hollow particles are not easily broken even when pressurized, and the hollow structure can be maintained, so it is easy to maintain the thermal insulation of the sheet 10. Thermoplastic polymers can be, for example, polymers containing acrylonitrile, vinylidene chloride, etc. as monomer units. The thickness of the shell can be more than 0.005 μm, or less than 15 μm.
[0043] The second hollow particle 112 contains, for example, a gas in the hollow part thereof. The second hollow particle 112 contains, for example, a gas at normal temperature and pressure (for example, at least at atmospheric pressure and 30° C.). The second hollow particle 112 may contain a liquid in addition to a gas.
[0044] As the components contained in the hollow part of the second hollow particle 112, for example, there can be mentioned hydrocarbons such as propane, propylene, butene, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, isohexane, heptane, isooctane, n-octane, isoalkanes (carbon number: 10 to 13), petroleum ether, etc.; low boiling point compounds such as methane halides and tetraalkylsilane; decomposition products of compounds that are gasified by thermal decomposition of azodicarbonamide, etc. In addition, the component contained in the hollow part of the second hollow particle 112 may also be air.
[0045] From the viewpoint of improving thermal insulation, the average particle diameter of the second hollow particles 112 is preferably less than 150 μm, more preferably less than 120 μm, further preferably less than 100 μm, for example, can be more than 5 μm, more than 10 μm, more than 20 μm or more than 30 μm. The average particle diameter of the second hollow particles is measured by laser diffraction / scattering method (for example, using "SALD-7500nan o" manufactured by SHIMADZU CORPORATION).
[0046] The density of the second hollow particles 112 may be 500 kg / m 3 Below, 300kg / m 3 Below, 100kg / m 3 Below, 50kg / m 3 Below or 40kg / m 3 Below, can also be 10kg / m 3 Above or 20kg / m 3 The density of the second hollow particle 112 in this specification refers to the density measured by the tap density method. That is, the second hollow particle 112 (about 5 g) is put into a 10 mL measuring cylinder and tapped 50 times, and the volume at the top when stable is taken as the stable volume and the density is calculated using the following formula.
[0047] Density = initial input (kg) / volume at stable state (m 3 )
[0048] From the viewpoint that the sheet 10 is more preferably used as an insulating material in a reflow process (usually heated to 260° C.), the shrinkage start temperature of the second hollow particles 112 is preferably 150° C. or more, 170° C. or more, or 180° C. or more, and may be 260° C. or less, 240° C. or less, 220° C. or less, or 200° C. or less. The shrinkage start temperature of the second hollow particles 112 refers to the temperature at which the volume change reaches a maximum value in a curve of temperature (horizontal axis)-volume change (vertical axis) when the temperature is increased at a heating rate of 10° C. / min by thermomechanical analysis (TMA).
[0049] From the viewpoint of improving the thermal insulation properties of the sheet 10, the content of the second hollow particles 112 (the content at atmospheric pressure and 30°C. The same applies hereinafter) is preferably 1 mass % or more, more preferably 3 mass % or more, further preferably 5 mass % or more, for example, can be 20 mass % or less, based on the total mass of the thermal insulation layer 11.
[0050] From the viewpoint of improving the thermal insulation of the sheet 10 , the content of the second hollow particles 112 is preferably 50 volume % or more, more preferably 60 volume % or more, and for example 95 volume % or less, based on the total volume of the thermal insulation layer 11 .
[0051] The mass ratio of the content of the second hollow particles relative to the content of the first hollow particles (the content (mass) of the second hollow particles / the content (mass) of the first hollow particles) is preferably 1 / 5 or more, more preferably 1 / 3 or more. The mass ratio of the content of the second hollow particles relative to the content of the first hollow particles is preferably 3 or less, more preferably 2 or less, and further preferably 1 or less.
[0052] The volume ratio of the content of the second hollow particles to the content of the first hollow particles (content (volume) of the second hollow particles / content (volume) of the first hollow particles) is preferably 10 or more, more preferably 15 or more. The volume ratio of the content of the second hollow particles to the content of the first hollow particles is preferably 80 or less, more preferably 60 or less, and further preferably 45 or less.
[0053] The heat-insulating layer 11 may further contain inorganic hollow particles. The inorganic hollow particles have an outer shell and a hollow portion. The outer shell of the inorganic hollow particles is composed of an inorganic material. The inorganic material may be, for example, inorganic glass such as borosilicate glass (sodium borosilicate glass, etc.), aluminosilicate glass, and glass obtained by combining these. The hollow portion of the inorganic hollow particles may contain, for example, a gas. The inorganic hollow particles may contain a gas at, for example, normal temperature and pressure (for example, at least at atmospheric pressure and 30° C.).
[0054] Based on the total mass of the sheet 10, the total content of the hollow particles (the total content of the first hollow particles 111, the second hollow particles 112 and the inorganic hollow particles at atmospheric pressure and 30°C. The same applies below) can be, for example, greater than 4 mass%, greater than 8 mass% or greater than 10 mass%, or less than 40 mass%, less than 35 mass% or less than 30 mass%.
[0055] The total content of the hollow particles may be, for example, 50% by volume or more, 60% by volume or more, or 70% by volume or more, or 95% by volume or less, based on the total volume of the sheet 10 .
[0056] The matrix polymer 113 is a polymer (binder polymer) that serves as a matrix (forms a continuous phase) for holding other materials contained in the heat insulating layer 11. The first hollow particles 111 and the second hollow particles 112 can be held by the matrix polymer 113 and dispersed in the matrix polymer 113.
[0057] The matrix polymer 113 may include a compound represented by the following formula (1) as a monomer unit. In other words, the matrix polymer 113 may be a polymer of a polymerizable compound including a compound represented by the following formula (1).
[0058]
[0059] In formula (1), R 11 and R 12 Each independently represents a hydrogen atom or a methyl group, R 13 It represents a divalent group having a polyoxyalkylene chain.
[0060] When the matrix polymer 113 contains the compound represented by the above formula (1) as a monomer unit, the heat insulating layer 11 has low elasticity and excellent elongation, and thus the followability of the sheet 10 to the adherend can be improved.
[0061] In one embodiment, R 11 and R 12 In another embodiment, one of R may be a hydrogen atom and the other may be a methyl group. 11 and R 12 Both of them can be hydrogen atoms. In other embodiments, R 11 and R 12 Both of these may be methyl groups.
[0062] In one embodiment, the polyoxyalkylene chain includes a structural unit represented by the following formula (2). This can improve the strength of the heat insulating layer 11.
[0063]
[0064] At this time, R 13 It may be a divalent group having a polyoxyethylene chain, and the compound represented by the formula (1) is preferably a compound represented by the following formula (1-2) (polyethylene glycol di(meth)acrylate).
[0065]
[0066] In formula (1-2), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning as , and m is an integer greater than 2.
[0067] In another embodiment, the polyoxyalkylene chain includes a structural unit represented by the following formula (3).
[0068]
[0069] At this time, R 13 It may be a divalent group having a polyoxypropylene chain, and the compound represented by the formula (1) is preferably a compound represented by the following formula (1-3) (polypropylene glycol di(meth)acrylate).
[0070]
[0071] In formula (1-3), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning as , and n is an integer greater than 2.
[0072] In another embodiment, the polyoxyalkylene chain is preferably a copolymer chain comprising the structural unit represented by the above formula (2) and the structural unit represented by the formula (3). The copolymer chain may be any of an alternating copolymer chain, a block copolymer chain or a random copolymer chain. The copolymer chain is preferably a random copolymer chain.
[0073] In each of the above embodiments, the polyoxyalkylene chain may have, as a structural unit, an oxyalkylene group having 4 to 5 carbon atoms such as an oxymethylene group, an oxybutylene group, or an oxypentylene group, in addition to the structural unit represented by formula (2) and the structural unit represented by formula (3).
[0074] R 13It may be a divalent group having other organic groups in addition to the above-mentioned polyoxyalkylene chain. Other organic groups may be chain groups other than the polyoxyalkylene chain, for example, a methylene chain (a chain with -CH2- as a structural unit), a polyester chain (a chain containing -COO- in a structural unit), a polyurethane chain (a chain containing -OCON- in a structural unit), etc.
[0075] For example, the compound represented by formula (1) may be a compound represented by the following formula (1-4).
[0076]
[0077] In formula (1-4), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning, R 14 and R 15 Each of k1, k2 and k3 is independently an alkylene group having 2 to 5 carbon atoms, and each of k1, k2 and k3 is independently an integer greater than 2. For example, k2 may be an integer less than 16.
[0078] There are multiple R 14 and R 15 They may be the same or different from each other. 14 and R 15 Preferably, they contain ethylene and propylene, respectively. 14 O) k1 The polyoxyalkylene chain represented by (R 15 O) k3 The polyoxyalkylene chains represented by are preferably copolymer chains containing an oxyethylene group (a structural unit represented by the above formula (2)) and an oxypropylene group (a structural unit represented by the above formula (3)).
[0079] In each of the above-mentioned embodiments, the number of oxyalkylene groups in the polyoxyalkylene chain is preferably 100 or more. When the number of oxyalkylene groups in the polyoxyalkylene chain is 100 or more, the elongation of the heat insulating layer 11 is further improved by lengthening the main chain of the compound represented by formula (1), and the strength of the heat insulating layer 11 can also be improved. The number of oxyalkylene groups corresponds to m in formula (1-2), n in formula (1-3), and k1 and k3 in formula (1-4), respectively.
[0080] The number of oxyalkylene groups in the polyoxyalkylene chain is more preferably 130 or more, 180 or more, 200 or more, 220 or more, 250 or more, 270 or more, 300 or more, or 320 or more. The number of oxyalkylene groups in the polyoxyalkylene chain may be 600 or less, 570 or less, or 530 or less.
[0081] From the viewpoint that the heat insulating layer 11 has low elasticity and excellent elongation, the weight average molecular weight of the compound represented by formula (1) is preferably 5000 or more, 6000 or more, 7000 or more, 8000 or more, 9000 or more, 10000 or more, 11000 or more, 12000 or more, 13000 or more, 14000 or more, or 15000 or more. The weight average molecular weight of the compound represented by formula (1) is preferably 100000 or less, 80000 or less, 60000 or less, 34000 or less, 31000 or less, or 28000 or less.
[0082] The matrix polymer 113 may contain only the compound represented by formula (1) as a monomer unit. The matrix polymer 113 may further contain other polymerizable compounds (details will be described later) other than the compound represented by formula (1) as a monomer unit. At this time, from the viewpoint that the thermal insulation layer 11 is lower elastic and has excellent elongation, the content of the compound represented by formula (1) is preferably 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more relative to the total of 100 parts by mass of the compound represented by formula (1) and other polymerizable compounds (hereinafter referred to as "the total content of the monomer unit"). The content of the compound represented by formula (1) can be 80 parts by mass or less, 70 parts by mass or less, or 60 parts by mass or less relative to the total of 100 parts by mass of the content of the monomer unit.
[0083] Other polymerizable compounds (monomer units) may be, for example, compounds having one (meth)acryloyl group. Such compounds may be, for example, alkyl (meth)acrylates. Other polymerizable compounds may be compounds having, in addition to one (meth)acryloyl group, an aromatic hydrocarbon group, a group containing a polyoxyalkylene chain, a group containing a heterocyclic ring, an alkoxy group, a phenoxy group, a group containing a silyl group, a group containing a siloxane bond, a halogen atom, a hydroxyl group, a carboxyl group, an amino group, or an epoxy group. In particular, the matrix polymer 113 contains, in addition to the (meth)acryloyl group, a compound having a hydroxyl group, a carboxyl group, an amino group, or an epoxy group, thereby further improving the adhesion of the thermal insulation layer 11 to other components.
[0084] The alkyl group (alkyl part other than the (meth)acryloyl group) in the alkyl (meth)acrylate may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group may be, for example, 1 to 30. The number of carbon atoms in the alkyl group may be 1 to 11, 1 to 8, 1 to 6, or 1 to 4, or may be 12 to 30, 12 to 28, 12 to 24, 12 to 22, 12 to 18, or 12 to 14.
[0085] Examples of the alkyl (meth)acrylate having a linear alkyl group include alkyl (meth)acrylate having a linear alkyl group having 1 to 11 carbon atoms and alkyl (meth)acrylate having a linear alkyl group having 12 to 30 carbon atoms.
[0086] Examples of the alkyl (meth)acrylate having a linear alkyl group having 1 to 11 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and undecyl (meth)acrylate.
[0087] Examples of the alkyl (meth)acrylate having a linear alkyl group having 12 to 30 carbon atoms include dodecyl (meth)acrylate (lauryl (meth)acrylate), tetradecyl (meth)acrylate, hexadecyl (meth)acrylate (cetyl (meth)acrylate), octadecyl (meth)acrylate (stearyl (meth)acrylate), behenyl (meth)acrylate (behenyl (meth)acrylate), eicosyl (meth)acrylate, triacontyl (meth)acrylate, and dioctadecyl (meth)acrylate.
[0088] Examples of the alkyl (meth)acrylate having a branched alkyl group include alkyl (meth)acrylate having a branched alkyl group having 1 to 11 carbon atoms and alkyl (meth)acrylate having a branched alkyl group having 12 to 30 carbon atoms.
[0089] Examples of the alkyl (meth)acrylate having a branched alkyl group having 1 to 11 carbon atoms include sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, isopentyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, and isodecyl (meth)acrylate.
[0090] Examples of the alkyl (meth)acrylate having a branched alkyl group having 12 to 30 carbon atoms include isomyristyl (meth)acrylate, 2-propylheptyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, isostearyl (meth)acrylate, and decyltetradecyl (meth)acrylate.
[0091] Examples of the alkyl (meth)acrylate having an alicyclic (cyclic) alkyl (cycloalkyl) group include cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, terpene (meth)acrylate, and dicyclopentanyl (meth)acrylate.
[0092] Examples of the compound having a (meth)acryloyl group and an aromatic hydrocarbon group include benzyl (meth)acrylate and the like.
[0093] Examples of the compound having a (meth)acryloyl group and a polyoxyalkylene chain-containing group include polyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, polybutylene glycol (meth)acrylate, and methoxypolybutylene glycol (meth)acrylate.
[0094] Examples of the compound having a (meth)acryloyl group and a heterocyclic ring-containing group include tetrahydrofurfuryl (meth)acrylate and the like.
[0095] Examples of the compound having a (meth)acryloyl group and an alkoxy group include 2-methoxyethyl acrylate and the like.
[0096] As a compound which has a (meth)acryloyl group and a phenoxy group, phenoxyethyl (meth)acrylate etc. are mentioned.
[0097] Examples of the compound having a (meth)acryloyl group and a silyl group-containing group include 3-acryloxypropyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-acryloxydecyltriethoxysilane.
[0098] As a compound which has a (meth)acryloyl group and a siloxane bond-containing group, siloxane (meth)acrylate etc. are mentioned.
[0099] Examples of the compound having a (meth)acryloyl group and a halogen atom include trifluoromethyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 1,1,1,3,3,3-hexafluoro-2-propyl (meth)acrylate, perfluoroethyl methyl (meth)acrylate, perfluoropropyl methyl (meth)acrylate, perfluorobutyl methyl (meth)acrylate, perfluoropentyl methyl (meth)acrylate, perfluorohexyl methyl (meth)acrylate, perfluoroheptyl methyl (meth)acrylate, perfluorooctyl methyl (meth)acrylate, perfluorononyl methyl (meth)acrylate, perfluorodecyl methyl (meth)acrylate, perfluoroundecyl methyl (meth)acrylate, perfluorododecyl methyl (meth)acrylate, and perfluorobutyl methyl (meth)acrylate. (Meth)acrylates having fluorine atoms, such as perfluorotridecylmethyl (meth)acrylate, perfluorotetradecylmethyl (meth)acrylate, 2-(trifluoromethyl)ethyl (meth)acrylate, 2-(perfluoroethyl)ethyl (meth)acrylate, 2-(perfluoropropyl)ethyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 2-(perfluoropentyl)ethyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 2-(perfluoroheptyl)ethyl (meth)acrylate, 2-(perfluorooctyl)ethyl (meth)acrylate, 2-(perfluorononyl)ethyl (meth)acrylate, 2-(perfluorotridecyl)ethyl (meth)acrylate, and 2-(perfluorotetradecyl)ethyl (meth)acrylate.
[0100] Examples of the compound having a (meth)acryloyl group and a hydroxyl group include hydroxyalkyl (meth)acrylates and hydroxyalkylcycloalkane (meth)acrylates. Examples of the hydroxyalkyl (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. Examples of the hydroxyalkylcycloalkane (meth)acrylates include (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.
[0101] Examples of the compound having a (meth)acryloyl group and a carboxyl group include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, monohydroxyethyl acrylate phthalate (for example, "ARONIX M5400" manufactured by TOAGOSEI CO., LTD.), and 2-acryloyloxyethyl succinate (for example, "NK ESTER A-SA" manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.).
[0102] Examples of the compound having a (meth)acryloyl group and an amino group include N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate.
[0103] Examples of the compound having a (meth)acryloyl group and an epoxy group include glycidyl (meth)acrylate, α-ethyl glycidyl (meth)acrylate, α-n-propyl glycidyl (meth)acrylate, α-n-butyl glycidyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 4,5-epoxypentyl (meth)acrylate, 6,7-epoxyheptyl (meth)acrylate, α-ethyl (meth)acrylate-6,7-epoxyheptyl (meth)acrylate, 3-methyl-3,4-epoxybutyl (meth)acrylate, 4-methyl-4,5-epoxypentyl (meth)acrylate, 5-methyl-5,6-epoxyhexyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, and α-ethyl (meth)acrylate-β-methyl glycidyl.
[0104] The matrix polymer 113 may contain one or more of the above-mentioned other polymerizable compounds as a monomer unit, and may or may not contain the compound represented by formula (1).
[0105] The content of the matrix polymer 113 based on the total mass of the heat insulating layer 11 may be, for example, 40 mass % or more, 50 mass % or more, 60 mass % or more, or 70 mass % or less, or 95 mass % or less or 90 mass % or less.
[0106] The heat insulating layer 11 may further contain other additives as needed. Examples of other additives include plasticizers, antioxidants (e.g., phenolic antioxidants), surface modifiers (e.g., silane coupling agents), dispersants, curing accelerators, colorants, crystal nucleating agents, thermal stabilizers, foaming agents, flame retardants, vibration dampers, dehydrating agents, flame retardant aids (e.g., metal oxides), etc. Based on the total mass of the heat insulating layer 11, the content of other additives may be 0.1% by mass or more, or 30% by mass or less.
[0107] The thickness of the heat insulating layer 11 may be, for example, 100 μm or more, 200 μm or more, or 500 μm or less, or 10 mm or less, 5 mm or less, or 2 mm or less.
[0108] The pressure-sensitive adhesive layer 12 may include a known pressure-sensitive adhesive, such as an acrylic pressure-sensitive adhesive, an epoxy pressure-sensitive adhesive, etc. The acrylic pressure-sensitive adhesive may include, for example, an acrylic copolymer and a cross-linking agent.
[0109] The acrylic copolymer is a copolymer of two or more polymerizable compounds. The two or more polymerizable compounds include one or more compounds having a (meth)acryloyl group. The acrylic copolymer includes one or more compounds having a (meth)acryloyl group as monomer units, but may also include two or more, three or more, or four or more compounds having a (meth)acryloyl group as monomer units.
[0110] The compound having a (meth)acryloyl group may be, for example, an alkyl (meth)acrylate. The alkyl group (the alkyl part other than the (meth)acryloyl group) in the alkyl (meth)acrylate may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group may be, for example, 1 to 30. The number of carbon atoms in the alkyl group may be 2 or more, 3 or more, or 25 or less, 20 or less, 15 or less, 10 or less, 7 or less, or 5 or less.
[0111] Examples of the compound having a (meth)acryloyl group include (meth)acrylic acid alkyl esters having a linear alkyl group having 1 to 11 carbon atoms, (meth)acrylic acid alkyl esters having a branched alkyl group having 1 to 11 carbon atoms, compounds having a (meth)acryloyl group and a heterocyclic ring-containing group, compounds having a (meth)acryloyl group and a hydroxyl group, and compounds having a (meth)acryloyl group and a carboxyl group.
[0112] As the (meth)acrylic acid alkyl ester having a straight-chain alkyl group with 1 to 11 carbon atoms, methyl (meth)acrylate, butyl (meth)acrylate, etc. can be mentioned. As the (meth)acrylic acid alkyl ester having a branched alkyl group with 1 to 11 carbon atoms, 2-ethylhexyl (meth)acrylate, etc. can be mentioned. As the compound having a (meth)acryloyl group and a heterocyclic ring-containing group, N-acryloylmorpholine (AC MO) and the like can be mentioned. As the compound having a (meth)acryloyl group and a hydroxyl group, 2-hydroxyethyl (meth)acrylate and the like can be mentioned. As the compound having a (meth)acryloyl group and a carboxyl group, (meth)acrylic acid and the like can be mentioned.
[0113] The acrylic copolymer may contain other polymerizable compounds other than the compound having a (meth)acryloyl group as monomer units. Examples of other polymerizable compounds (monomer units) in the acrylic copolymer include acrylonitrile.
[0114] The weight average molecular weight (Mw) of the acrylic copolymer may be 100,000 or more, 200,000 or more, 400,000 or more, 500,000 or more, or 600,000 or more, or 1.2 million or less, 1.1 million or less, or 1 million or less.
[0115] The content of the acrylic copolymer may be 70% by mass or more, or 80% by mass or more, or 98% by mass or less, or 95% by mass or less, based on the total mass of the pressure-sensitive adhesive layer 12 .
[0116] The crosslinking agent may be, for example, a crosslinking agent having an epoxy group, a crosslinking agent having an isocyanate group, etc. The crosslinking agent having an epoxy group may have 2 or more, 3 or more, or 4 or more epoxy groups. Examples of crosslinking agents having 4 epoxy groups include N,N,N',N'-tetraglycidyl-1,3-bis(aminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-m-xylene diamine.
[0117] The cross-linking agent having an isocyanate group may have two or more isocyanate groups or three or more isocyanate groups. An example of a cross-linking agent having three isocyanate groups is "CORONATE L" (manufactured by TOSOH CORPORATION).
[0118] The thickness of the pressure-sensitive adhesive layer 12 may be, for example, 5 μm or more or 10 μm or more, or 200 μm or less, 100 μm or less, or 50 μm or less.
[0119] like Figure 1 In one embodiment shown, the sheet 10 may be composed only of the heat insulating layer 11 and the pressure sensitive adhesive layer 12. In another embodiment, the sheet may also have other layers in addition to the heat insulating layer and the pressure sensitive adhesive layer. In this case, in the sheet, the heat insulating layer and the pressure sensitive adhesive layer may be in contact with each other (may not be stacked via other layers), and the heat insulating layer and the pressure sensitive adhesive layer may also be stacked via other layers. As examples of other layers, a surface protection layer, an adhesive layer, and a support layer may be cited.
[0120] In one embodiment, the sheet material having other layers may be a sheet material having a surface protection layer (first surface protection layer), a heat insulating layer, an adhesive layer (first adhesive layer), a support layer (first support layer), an adhesive layer (second adhesive layer), a support layer (second support layer), a pressure-sensitive adhesive layer and a surface protection layer (second surface protection layer). The surface protection layer may be, for example, composed of a resin film (PET film, etc.) having a surface in contact with the heat insulating layer or the pressure-sensitive adhesive layer and subjected to an easy-to-peel treatment. The adhesive layer may contain, for example, an acrylic adhesive, an epoxy adhesive, etc. The support layer may be, for example, composed of a resin film (polyimide film, etc.).
[0121] The thickness of the sheet 10 may be, for example, 100 μm or more, 200 μm or more, or 500 μm or less, or 11 mm or less, 5 mm or less, 3 mm or less, or 2 mm or less.
[0122] The sheet 10 can be manufactured, for example, by separately preparing the heat insulating layer 11 and the pressure sensitive adhesive layer 12, and bonding the heat insulating layer 11 to the pressure sensitive adhesive layer 12. For example, the manufacturing method of the sheet having the above-mentioned other layers may include: the steps of separately preparing a laminate A of a surface protective layer (first surface protective layer) and a heat insulating layer, a laminate B of an adhesive layer (first adhesive layer), a support layer (first support layer) and an adhesive layer (second adhesive layer), and a laminate C of a support layer (second support layer), a pressure sensitive adhesive layer and a surface protective layer (second surface protective layer); and the steps of bonding the heat insulating layer of the laminate A to the adhesive layer (first adhesive layer) of the laminate B, and bonding the adhesive layer (second adhesive layer) of the laminate B to the support layer (second support layer) of the laminate C.
[0123] The laminate A is obtained, for example, by the following method: after preparing the above-mentioned first hollow particles, the second hollow particles and a mixture containing a polymerizable compound, the polymerizable compound in the mixture is polymerized on the surface protective layer (first surface protective layer) to form a matrix polymer. As laminate B, for example, a double-sided adhesive tape having a support layer (first support layer) and an adhesive layer (first adhesive layer) and an adhesive layer (second adhesive layer) respectively arranged on both sides of the support layer can be used. Laminate C is obtained, for example, by the following method: a pressure-sensitive adhesive composition obtained by mixing materials such as acrylic pressure-sensitive adhesives is applied to the surface protective layer (second surface protective layer), and after the pressure-sensitive adhesive composition is dried and / or the curing component in the pressure-sensitive adhesive composition is cured to form a pressure-sensitive adhesive layer, a support layer (second support layer) is arranged on the surface of the pressure-sensitive adhesive layer on the opposite side of the surface protective layer (second surface protective layer). In the process of laminating laminate A, laminate B and laminate C, for example, a roll laminator can be used.
[0124] Example
[0125] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0126] <Insulation layer>
[0127] To prepare the thermal insulation layer, the following components were used.
[0128] (First hollow particle)
[0129] A: "MATSUMOTO MICROSPHER E FN-190SSD" manufactured by Matsumoto Yushi-Seiyaku Co., Ltd. (average particle size: 10 to 15 μm, maximum volume expansion ratio: 50 times or more, expansion start temperature: 190°C, maximum expansion temperature: 210 to 220°C)
[0130] (Second hollow particle)
[0131] B: "Expancel 920DE80d30" manufactured by Japan Fillite Co., Ltd. (average particle size 60-90 μm, density 30±3 kg / m 3 , Maximum volume expansion ratio: less than 5 times, Shrinkage start temperature: 200℃)
[0132] (Polymerizable compound)
[0133] C-1: A mixture of compounds represented by the following formula (1-5) synthesized by the sequence shown below (weight average molecular weight: 15000, m1+m2 in formula (1-5) is approximately an integer of 252±5, and n1+n2 is approximately an integer of 63±5 (wherein m1, m2, n1 and n2 are each an integer greater than 2, m1+n1≥100, and m2+n2≥100))
[0134]
[0135] [In formula (1-5), -r- represents the symbol of random copolymerization.]
[0136] C-2: Dicyclopentanyl acrylate ("FANC RYL FA-513A" manufactured by Showa Denko Materials co., Ltd.)
[0137] C-3: 4-Hydroxybutyl acrylate (manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD.)
[0138] (Other ingredients)
[0139] D: polymerization initiator ("PERBUTYL O" manufactured by NOF CORPORATION)
[0140] E: Phenolic antioxidant ("Irganox 1010" manufactured by BASF Japan Ltd.)
[0141] F: Surface conditioning agent ("BYK350" manufactured by BYK Co., Ltd.)
[0142] [Synthesis of the compound represented by formula (1-5)]
[0143] A 500 mL flask consisting of a stirrer, a thermometer, a nitrogen inlet pipe, a discharge pipe and a heating jacket was used as a reactor, and 225 g of a diol having a polyoxyalkylene chain ("NEWPOL 75H-90000" manufactured by SANYO CHEMICAL INDUSTRIES, LTD.) and 300 g of toluene were added to the reactor, stirred at 45°C and a stirring speed of 250 times / min, and nitrogen was flowed at 100 mL / min, and stirred for 30 minutes. Then, the temperature was lowered to 25°C, and after the temperature was lowered, 2.9 g of acryloyl chloride was added dropwise to the reactor and stirred for 30 minutes. Then, 3.8 g of triethylamine was added dropwise and stirred for 2 hours. Then, the temperature was raised to 45°C and the reaction was carried out for 2 hours. The reaction solution was filtered, the filtrate was desolvated, and the compound represented by formula (1-5) was obtained.
[0144] [Production of thermal insulation layer]
[0145] The components in the amounts shown in Table 1 were mixed to obtain a composition for making a heat insulating layer. Two sets of molded plates with a release-treated polyester sheet ("A31" manufactured by TOYOBO CO., LTD.) with a length of 200 mm × a width of 200 mm × a thickness of 5 mm were prepared, with the release-treated surface facing upward. A silicone rubber mold frame (200 mm × 200 mm) with a hole of 120 mm × 120 mm × 2.0 mm was set on the release-treated surface of one molded plate, and the composition for making a heat insulating layer was filled inside the mold frame. Moreover, the release-treated surface of another molded plate was set as the composition side, and after covering with the upper cover, it was heated at 135°C for 40 minutes. Then, one molded plate, the silicone rubber mold frame and the glass plate in the other molded plate were removed to produce a laminate (laminate A) of a surface protective layer (polyester sheet) and a heat insulating layer (thickness 2.0 mm). Then, by peeling off the surface protective layer of the laminate A, a heat insulating layer was obtained.
[0146] [Evaluation of thermal insulation properties]
[0147] The thermal conductivity of the heat insulating layer used in each example and comparative example was measured by the following procedure. The heat insulating layer was cut into 8 cm × 13 cm × 2.0 mm, sandwiched between a reference plate and a measuring probe, and the thermal conductivity (initial thermal conductivity) was measured at 25°C using a rapid thermal conductivity meter ("QTM-710" manufactured by KYOTO ELECTRONICS MANUFACTURING CO., LTD., measuring probe PD-11N, thin film measurement mode). In addition, the heat insulating layer was cut into a width of 20 mm × a length of 50 mm to prepare a test piece of the heat insulating layer, and the test piece was passed through a reflow oven (TNP25-337EM series N2 reflow device manufactured by TAMURA CORPORATION) to apply a heat history, and after natural cooling, the thermal conductivity (heated thermal conductivity) was measured in the same manner as above. Specifically, the thermal history was applied by heating from room temperature (25°C) to 200°C at a heating rate of 47°C / min in a reflow oven, and then heating from 200°C to 260°C at a heating rate of 38°C / min. And, specifically, natural cooling was cooling to 60°C in the reflow oven, taking it out of the reflow oven and cooling it to 25°C. For the reference sample, two polyester sheets ("A31" manufactured by TOYOBO CO., LTD.) subjected to mold release were overlapped and clamped with a reference plate and a measurement probe for measurement. The results are shown in Table 1.
[0148] [Volume change rate of the insulation layer]
[0149] The prepared insulation layer was cut into pieces of 2 cm × 6 cm × 0.2 cm (volume: 2.4 cm 3 ) to make a test piece, and the test piece was subjected to a heat history using a reflow oven in the same manner as in the above [Evaluation of Thermal Insulation] and naturally cooled. Then, the thickness of the test piece at 5 locations was measured with a micrometer to calculate the average thickness, and the width of the test piece at 5 locations was measured with a vernier caliper to calculate the average width. In addition, the length of one location of the test piece was measured with a vernier caliper. Using the obtained value, the volume after heating was calculated by the following formula.
[0150] Volume after heating [cm 3 ] = (average value of thickness) × (average value of width) × (measured value of length)
[0151] The volume change rate was calculated using the following formula.
[0152] Volume change rate [%] = {((volume after heating [cm 3 ])-2.4) / 2.4}×100
[0153] <Pressure-sensitive adhesive layer>
[0154] In each of the Examples and Comparative Examples, any one of the pressure-sensitive adhesive layers a to e produced by the following procedure was used.
[0155] [Preparation of pressure-sensitive adhesive layer a]
[0156] As the monomer unit, an acrylic copolymer (weight average molecular weight: 200,000) containing 2-ethylhexyl acrylate (EHA) and 2-hydroxyethyl acrylate (HEA) at a ratio of EHA:HEA=65:35 on a mass basis was used. 100 parts by mass of an ethyl acetate solution of the acrylic copolymer (solid content: 35% by mass), 5 parts by mass of an isocyanate (trade name: CORONATE L, manufactured by TOSOH CORPORATION) as a crosslinking agent, 7 parts by mass of a 10-functional urethane acrylate (trade name: U-10PPA, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.) as a photocurable resin, and 0.21 parts by mass of a photopolymerization initiator (trade name: Irgcure 819, manufactured by BASF) were dissolved in a mixed solvent of toluene and methyl ethyl ketone so that the solid content was 25% by mass. Next, the mixture was stirred at a rotation speed of 1000 rpm for 5 minutes using an autorotation and revolution stirrer, and then left to stand at room temperature until bubbles disappeared, thereby obtaining a pressure-sensitive adhesive composition.
[0157] The obtained pressure-sensitive adhesive composition was applied to the easily releasable surface of a 38 μm thick polyester film (trade name: PUREX A31, manufactured by TOYOBO CO., LTD.) having one side subjected to an easily releasable treatment using a silicone release agent, and then dried in a drying oven at 100° C. for 2 minutes and at 300 mJ / cm 2 The photocurable resin was cured by irradiation with ultraviolet light of a wavelength of 365 nm to form a pressure-sensitive adhesive layer with a thickness of 10 μm. Then, at room temperature (25°C), a polyimide film substrate with a thickness of 25 μm (trade name: KAPTON 100H, manufactured by DUPONT-TORAY CO., LTD.) was laminated on the exposed surface of the formed pressure-sensitive adhesive layer to prepare a laminate (laminate C with a pressure-sensitive adhesive layer a) in which a surface protective layer (polyester film), a pressure-sensitive adhesive layer a and a support layer (polyimide film substrate) were laminated in sequence. In addition, by peeling off the surface protective layer of the laminate C with a pressure-sensitive adhesive layer a, a pressure-sensitive adhesive layer a with a support layer was obtained.
[0158] [Preparation of pressure-sensitive adhesive layer b]
[0159] Instead of the above-mentioned acrylic copolymer, an acrylic copolymer (weight average molecular weight: 200,000) containing methyl acrylate (MA), 2-ethylhexyl acrylate (EHA), acrylic acid (AA), and 2-hydroxyethyl acrylate (HEA) in a ratio of MA:EHA:AA:HEA = 50:40:0.5:9.5 on a mass basis was used as a monomer unit. In addition, a laminate C having a pressure-sensitive adhesive layer b and a pressure-sensitive adhesive layer b with a support layer were prepared in the same manner as the pressure-sensitive adhesive layer a.
[0160] [Preparation of pressure-sensitive adhesive layer c]
[0161] A laminate C including a pressure-sensitive adhesive layer c and a pressure-sensitive adhesive layer c with a support layer were prepared in the same manner as in the pressure-sensitive adhesive layer b, except that the amount of isocyanate as a cross-linking agent was changed to 2.4 parts by mass.
[0162] [Preparation of pressure-sensitive adhesive layer d]
[0163] As a monomer unit, an acrylic copolymer (weight average molecular weight: 670,000 to 950,000) containing butyl acrylate (BA), acrylonitrile (AN) and acrylic acid (AA) at a ratio of BA:AN:AA=85:7.5:7.5 on a mass basis was prepared. This acrylic copolymer, "TETRAD X" manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC. as a crosslinking agent, "NONFLEX DCD" (4,4-bis(α,α-dimethylbenzyl)diphenylamine) manufactured by Seiko Chemical Co., Ltd. as an antioxidant, and toluene and methyl ethyl ketone (MEK) as solvents were used. The components were mixed in a ratio of acrylic copolymer: crosslinking agent: antioxidant: toluene: MEK = 80.62: 8.47: 0.60: 8.25: 2.06 on a mass basis, stirred at a rotation speed of 1000 rpm for 5 minutes with a rotary and revolving stirrer, and then placed at room temperature until the bubbles disappeared, thereby obtaining a pressure-sensitive adhesive composition. The obtained pressure-sensitive adhesive composition was applied to the easy-peeling treatment surface of a 38 μm thick polyester film (trade name: PUREX A31, manufactured by TOYOBO CO., LTD.) with a single side subjected to an easy-peeling treatment based on a silicone release agent, and then dried at 100° C. for 2 minutes in a drying oven to form a pressure-sensitive adhesive layer with a thickness of 10 μm. Next, a polyimide film substrate (trade name: KAPTON 100H, manufactured by DU PONT-TORAY CO., LTD.) with a thickness of 25 μm was laminated on the exposed surface of the formed pressure-sensitive adhesive layer at room temperature (25° C.), thereby preparing a laminate (laminate C having a pressure-sensitive adhesive layer d) in which a surface protective layer (polyester film), a pressure-sensitive adhesive layer d, and a support layer (polyimide film substrate) were laminated in this order. Furthermore, by peeling off the surface protective layer of the laminate C having the pressure-sensitive adhesive layer d, a pressure-sensitive adhesive layer d with a support layer was obtained.
[0164] [Preparation of pressure-sensitive adhesive layer e]
[0165] As a monomer unit, an acrylic copolymer containing butyl acrylate (BA) and acryloyl morpholine (ACMO) in a ratio of BA:ACMO=99.9:0.1 on a mass basis was prepared. The acrylic copolymer, 1,3-bis(diglycidylaminomethyl)cyclohexane as a crosslinking agent, "NONFLEX DCD" (4,4-bis(α,α-dimethylbenzyl)diphenylamine) manufactured by Seiko Chemical Co., Ltd. as an antioxidant, and ethyl acetate as a solvent were used. On a mass basis, these components were mixed in a ratio of acrylic copolymer: crosslinker: antioxidant: ethyl acetate = 43.41:1.18:0.59:54.82, and after stirring for 5 minutes at a speed of 1000 rpm by a self-rotating revolution mixer, it was placed at room temperature until the bubbles disappeared, thereby obtaining a pressure-sensitive adhesive composition. The obtained pressure-sensitive adhesive composition was applied to the easily releasable surface of a 38 μm thick polyester film (trade name: PUREX A31, manufactured by TOYOBO CO., LTD.) on one side of which an easy-releasable treatment based on a silicone release agent was applied, and then dried in a drying oven at 100°C for 2 minutes to form a 10 μm thick pressure-sensitive adhesive layer. Next, at room temperature (25°C), a 25 μm thick polyimide film substrate (trade name: KAPTON 100H, manufactured by DU PONT-TORAY CO., LTD.) was laminated on the exposed surface of the formed pressure-sensitive adhesive layer, thereby preparing a laminate (laminate C with a pressure-sensitive adhesive layer e) in which a surface protective layer (polyester film), a pressure-sensitive adhesive layer e and a support layer (polyimide film substrate) were laminated in sequence. In addition, by peeling off the surface protective layer of the laminate C with a pressure-sensitive adhesive layer e, a pressure-sensitive adhesive layer e with a support layer was obtained.
[0166] [Peel strength of pressure-sensitive adhesive layer]
[0167] The peel strength of each pressure-sensitive adhesive layer a to e was measured in the following order. A Si wafer with a length of 25 mm and a width of 70 mm and a pressure-sensitive adhesive layer with a support layer cut into a length of 20 mm and a width of 60 mm were prepared. A pressure-sensitive adhesive layer with a support layer was provided on the Si wafer so that the pressure-sensitive adhesive layer was in contact with the Si wafer and bubbles would not enter between the two. The Si wafer provided with a pressure-sensitive adhesive layer with a support layer was placed on a stainless steel plate with a length of 380 mm, a width of 500 mm, and a thickness of 0.5 mm, and a roller laminator ("VA-770H special laminator" manufactured by TAISEI LAMINATORCO.,LTD.) was used at a pressure of 6 kgf / cm 2The pressure-sensitive adhesive layer and the Si wafer were attached under the conditions of 0.2 rpm, a rotation speed of 0.2 rpm, and a temperature of 40°C to prepare the sample. The pressure-sensitive adhesive layer with a support layer of the obtained sample was cut to a width of 5 mm, and 10 mm on one side of the length direction was peeled off from the Si wafer, and the 90° peel strength (initial 90° peel strength) was measured by a tensile tester ("Autograph EZ-TEST EZ-S" manufactured by SHIMADZU CORPORATION). The results are shown in Table 1.
[0168] <Sheet>
[0169] [Sheet production]
[0170] Using a roll laminator (HOTDOG LMP-350EX manufactured by LAMI CORPORATION INC.), an adhesive tape (a tape having a support layer and adhesive layers provided on both sides of the support layer. Hi-Bon 11-652 manufactured by Showa Denko Materials Co., Ltd.) was laminated on the support layer side of the laminate C having each pressure-sensitive adhesive layer. Furthermore, using the above-mentioned roll laminator, the laminate A was laminated on the tape in a manner such that the tape was in contact with the heat insulating layer, thereby obtaining the sheets involved in Examples 1 to 8 and Comparative Examples 1 and 2. The thickness of the sheet was 2135 μm.
[0171] [Table 1]
[0172]
[0173] Explanation of symbols
[0174] 10 - sheet, 11 - heat insulating layer, 12 - pressure-sensitive adhesive layer, 111 - first hollow particles, 112 - second hollow particles, 113 - matrix polymer.
Claims
1. A sheet material comprising a heat insulating layer and a pressure-sensitive adhesive layer, The heat insulating layer contains first hollow particles which are heat-expandable organic hollow particles, second hollow particles which are organic hollow particles other than the first hollow particles, and a matrix polymer.
2. The sheet material according to claim 1, wherein The content of the first hollow particles is 1.5% by volume or more based on the total volume of the heat insulating layer.
3. The sheet material according to claim 1 or 2, wherein: The volume ratio of the content of the second hollow particles to the content of the first hollow particles is 45 or less.
4. The sheet material according to claim 1 or 2, wherein: The matrix polymer comprises, as a monomer unit, a compound represented by the following formula (1), In formula (1), R 11 and R 12 Each independently represents a hydrogen atom or a methyl group, R 13 It represents a divalent group having a polyoxyalkylene chain.
Citation Information
Patent Citations
Method of manufacturing magnetic recording apparatus and magnetic recording apparatus
JP2017224663A
Heat-sensitive recording medium
JP2008149623A
Thermosensitive recording linerless label
JP2021126860A
Thermal transfer recording medium
US20180326772A1